Sebelipase alfa for lysosomal acid lipase deficiency: 5‐year treatment experience from a phase 2 open‐label extension study. (9th August 2020) - Malinová, Vĕra; Balwani, Manisha; Sharma, Reena; Arnoux, Jean‐Baptiste; Kane, John; Whitley, Chester B.; Marulkar, Sachin; Abel, Florian
Abstract: Background and Aims: Lysosomal acid lipase deficiency is characterized by hepatomegaly and dyslipidaemia, which can lead to cirrhosis and premature atherosclerosis. Sebelipase alfa is an approved recombinant human lysosomal acid lipase. In an open‐label extension study of adults with lysosomal acid lipase deficiency (LAL‐CL04), sebelipase alfa treatment for 1 year reduced serum transaminase levels and liver fat content and improved serum lipid levels. Methods: Final data from LAL‐CL04 are reported herein for patients who received sebelipase alfa infusions (1.0 or 3.0 mg/kg every other week) for up to 5 years. Results: Of 8 patients enrolled, 7 received sebelipase alfa for 224‐260 weeks; 1 was lost to follow‐up. Median baseline levels of alanine aminotransferase and aspartate aminotransferase (81.5 and 50.0 U/L, respectively) were decreased through the end‐of‐study visit (54.0 and 34.0 U/L). Median low‐density lipoprotein cholesterol decreased from 113 to 78 mg/dL, total cholesterol decreased from 171 to 132 mg/dL, and high‐density lipoprotein cholesterol increased from 37 to 42 mg/dL. Most treatment‐emergent adverse events were nonserious (99%), mild/moderate (98%) and unrelated to sebelipase alfa (87%); no patient discontinued as a result of treatment‐emergent adverse events. One patient had 2 serious treatment‐emergent adverse events (cholecystitis and cholelithiasis; assessed as unlikely related to sebelipase alfa). Two patients had 20 nonserious infusion‐associated reactions in weeks 6‐38; all were manageable. One patient tested positive for antidrug antibodies (single occurrence). Conclusions: Sebelipase alfa was well tolerated and improved serum transaminase and lipid levels for up to 5 years in adults with lysosomal acid lipase deficiency. Trial registration number: ClinicalTrials.gov record NCT01488097.